2023
DOI: 10.3390/antibiotics12020233
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumonia in Sudan: Multidrug Resistance, Polyclonal Dissemination, and Virulence

Abstract: The emergence and global expansion of hyper-virulent and multidrug resistant (MDR) Klebsiella pneumoniae is an increasing healthcare threat worldwide. The epidemiology of MDR K. pneumoniae is under-characterized in many parts of the world, particularly Africa. In this study, K. pneumoniae isolates from hospitals in Khartoum, Sudan, have been whole-genome sequenced to investigate their molecular epidemiology, virulence, and resistome profiles. Eighty-six K. pneumoniae were recovered from patients in five hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…In total, 35 were CR, and 3/35 were not CPE. However, the study indicated that among the total 86 sequenced strains, 37 were CPE, encoding for NDM-1, NDM-4, NDM-5, OXA-48 and OXA-232; 3 strains presented both NDM-5 and OXA-48 [137].…”
Section: Resultsmentioning
confidence: 94%
“…In total, 35 were CR, and 3/35 were not CPE. However, the study indicated that among the total 86 sequenced strains, 37 were CPE, encoding for NDM-1, NDM-4, NDM-5, OXA-48 and OXA-232; 3 strains presented both NDM-5 and OXA-48 [137].…”
Section: Resultsmentioning
confidence: 94%
“…The results of this study are consistent with studies conducted in other LMICs (Ethiopia, 8 Zambia, 13 Peru 10 and Egypt 9 ), highlighting the poor link between different hospital wards and CMLs, lack of clinical specimens being sent for microbiological culture and susceptibility, and starting antibiotic treatment based on clinical findings, not being confirmed microbiologically (species and antibiogram). In a previous study, 14 we noted a surge in private laboratory diagnostic services that are replacing the hospital microbiology laboratories. Doctors are increasingly depending on outsourcing microbiological specimens, which results in poor and fragmented hospital data on burden and prevalence of bacteria and ABR.…”
Section: Discussionmentioning
confidence: 89%
“…on cerebrospinal fluid; 36.6% of the isolates were MDR of which 69.2% were Gram-negatives and 30.8% were Gram-positives [ 20 ]. Additionally, in Sudan, 80% of K. pneumoniae were reported as MDR [ 21 ], and one more study found that there was a high prevalence of MDR Enterobacteriaceae ; mainly ESBL-positive E. coli and K. pneumoniae [ 22 ], Whereas 18% of P. aeruginosa isolates were MDR in a recent work published in 2023 [ 23 ], and 89.2% of S. aureus were MDR, of them 67.6% were methicillin resistant [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%